Community Empowerment for the Development of Nai Nang Apiculture Learning Center as an Educational Tourism in Krabi Thailand - Suphattra Sangthong; Dr. Ir. Aldi Wisnumurti Sarwono, S.S., M.Hum., CHE., CGSP.; Weavy Kherenhapukh; Faisal Satriawan (International Journal Of Tourism, 2023)
Nai Nang Apiculture Learning Center is an educational tourism in the form of a bee farm area and is jointly managed by the community in the village of Nai Nang, Krabi, Thailand. This learning center has a main attraction in bee keeping, and has been processing bee products thanks to the empowerment of the surrounding community. However, it was observed that Nai Nang Apiculture Learning Center also has other several attractions that have not been developed by the community as the management. The tourism services provided by the community at the Nai Nang Apiculture Learning Center has not been optimized. The purpose of this research is to answer why community empowerment is needed for the development of educational tourism in Nai Nang Apiculture Learning Center and what is the form of community participation or support required for the development of educational tourism in Nai Nang Apiculture Learning Center. The research method used is descriptive qualitative. Data collection techniques by means of observation, interviews, and study of documents. The data were then analyzed using the SWOT analysis. The result of this research is that people need to get socialization about educational tourism services in Nai Nang Apiculture Learning Center, such as how to explain honey processing from the bee farm. Besides that, English language training needs to be carried out so that the community can more easily interact with foreign tourists. Additionally, the community can still develop a new source of tourist attraction, namely rubber trees plantation, thus adding more value and experiences on the educational tourism.